Lower Cross-Braced Truck and Swing Motion Truck Have Different Effect on Freight Car Dynamics Performance - Chao Chen; Yanhui Han; Mei Han (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
There are two major types of trucks for freight car in Chinese railroad. One is the lower cross-braced truck; the other is the swing motion truck. To evaluate the different performance, diamond resistant rigidity of the lower cross-braced truck and the lateral stiffness of the swing motion truck are analyzed. To simulate the dynamics performance of the swing motion truck, an equivalent lateral stiffness is calculated. Then it is modeled as a lateral spring between side frames and bolstered to simulate the swing. After that, two typical freight cars’ models which use the two types of trucks are built in SIMPACK. The L/V Ratio and Wheel Load Reduction Ratio are chosen for evaluating running safety of the freight car. The simulation results are compared and they prove that the impact force between wheel and rail when the car passing curve can be reduced effectively as the swing motion truck has a better lateral flexible. Therefore, it has a lower L/V ratio under the same running and loading condition. However, the swing leads a larger lateral displacement of the car-body, so the gravity center of loaded car has a larger lateral displacement than the car with lower cross-braced truck; which results to a larger Wheel Load Reduction Ratio. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2204